Copper‐Catalyzed Asymmetric Diyne Cyclization via [1, 2]‐Stevens‐Type Rearrangement for the Synthesis of Chiral Chromeno[3, 4‐c]pyrroles. Issue 7 (23rd December 2021) - Hong, Feng‐Lin; Shi, Chong‐Yang; Hong, Pan; Zhai, Tong‐Yi; Zhu, Xin‐Qi; Lu, Xin; Ye, Long‐Wu
Abstract: Here, we report a copper‐catalyzed asymmetric cascade cyclization/[1, 2]‐Stevens‐type rearrangement via a non‐diazo approach, leading to the practical and atom‐economic assembly of various valuable chiral chromeno[3, 4‐ c ]pyrroles bearing a quaternary carbon stereocenter in generally moderate to good yields with wide substrate scope and excellent enantioselectivities (up to 99 % ee). Importantly, this protocol not only represents the first example of catalytic asymmetric [1, 2]‐Stevens‐type rearrangement based on alkynes but also constitutes the first asymmetric formal carbene insertion into the Si−O bond . Abstract : A copper‐catalyzed asymmetric cascade cyclization/[1, 2]‐Stevens‐type rearrangement is disclosed, affording valuable chiral chromeno[3, 4‐ c ]pyrroles bearing a quaternary carbon stereocenter in generally moderate to good yields with excellent enantioselectivities. Importantly, this protocol represents the first catalytic asymmetric [1, 2]‐Stevens‐type rearrangement based on alkynes and the first asymmetric formal carbene insertion into the Si−O bond.